Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/mot.0000000000000915
|View full text |Cite
|
Sign up to set email alerts
|

Gender and racial disparities in the transplant surgery workforce

Abstract: Purpose of review This review explores trends in the United States (US) transplant surgery workforce with a focus on historical demographics, post-fellowship job market, and quality of life reported by transplant surgeons. Ongoing efforts to improve women and racial/ethnic minority representation in transplant surgery are highlighted. Future directions to create a transplant workforce that reflects the diversity of the US population are discussed. Recent findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
(58 reference statements)
4
9
0
Order By: Relevance
“…[ 48 ] Only 5.5% of transplant surgeons are Black, and 8% are Hispanic. [ 49 ] Prioritization on the recruitment and retention of diverse multidisciplinary teams are needed to provide the highest quality of care to the diverse populations we serve and to best address racial and ethnic health disparities and systemic racism in transplantation.…”
Section: Addressing Disparities In Pediatric Liver Transplantationmentioning
confidence: 99%
“…[ 48 ] Only 5.5% of transplant surgeons are Black, and 8% are Hispanic. [ 49 ] Prioritization on the recruitment and retention of diverse multidisciplinary teams are needed to provide the highest quality of care to the diverse populations we serve and to best address racial and ethnic health disparities and systemic racism in transplantation.…”
Section: Addressing Disparities In Pediatric Liver Transplantationmentioning
confidence: 99%
“…Transplant surgery is consistently the least competitive surgical subspecialty fellowship. 20,22 Reasons for not pursuing a career in transplantation include perceptions of a poor lifestyle, high call burden, poor operative experiences during transplant rotations in medical school or residency, and a limited job market. 22,23 Transplant fellowship programs also have an opportunity to use social media, showcasing their unique training environments while providing fellows to highlight their experiences.…”
Section: Recruitment Of a Diverse Inclusive And Talented Workforce In...mentioning
confidence: 99%
“…19 Nevertheless, a recent review found that diversity in transplant surgery has not substantially improved, with 12% identifying as female and only 5.5% identifying as Black and 8% as Hispanic. 20,21 Social media can also be leveraged by providing a platform for virtual interaction among students, trainees, and mentors to establish a mentorship relationship and foster a supportive path to a career in transplantation.…”
Section: Recruitment Of a Diverse Inclusive And Talented Workforce In...mentioning
confidence: 99%
“…Diversity helps to mitigate the harm of implicit biases that are inherent in us all; race concordance among providers has also been associated with better health outcomes and process measures for Black patients. 9,10 Increasing diversity among providers may also alleviate reported distrust and fears about organ donation and transplantation in socially disadvantaged communities. Unfortunately, diversity among transplant surgeons has been historically low, with only 5.5% self-identifying as Black, which mirrors the general surgery Black representation at 5%, whereas the White to non-White transplant workforce ratio has increased by 35% from 2000 to 2013.…”
mentioning
confidence: 99%
“…The National Institutes of Health has acknowledged that increasing diversity of the biomedical sciences workforce would improve health equity by increasing the capacity to identify, address, and eliminate health disparities. Diversity helps to mitigate the harm of implicit biases that are inherent in us all; race concordance among providers has also been associated with better health outcomes and process measures for Black patients 9 , 10 . Increasing diversity among providers may also alleviate reported distrust and fears about organ donation and transplantation in socially disadvantaged communities.…”
mentioning
confidence: 99%